Estudio comparativo de la efectividad en el control del Biofilm dental, con la técnica de bass modificada y la propia del paciente, en adultos jóvenes, que acuden al Centro de Atención Odontológica de la UDLA - Villagómez Pereira, Katherine Lucía (2018)
Objectives: To compare the effectiveness of dental biofilm control with the modified bass technique and technique used by the patient aged 18 to 60 who goes to the Dental Care Center of the UDLA. Clinically evaluate through the O Leary index the level of biofilm presented by patients at the beginning of the evaluation and after one week. Materials and Methods: The present investigation has a descriptive - comparative cross-sectional design. It works with a universe of 60 subjects divided into two groups of 30 and is dedicated to the evaluation of biofilm levels using the O Leary index to measure the amount of plaque in the two groups. The effectiveness of the techniques will be evaluated 7 days after having performed the first intervention, using the O'Leary index as a method to determine that the highest production was in the elimination of the biofilm. Results: The most efficient technique for the elimination of the biofilm is the Modified Bass technique with a percentage ratio of 17.9% compared to the technique used by the patient, whose percentage value of the plate index is 25.1%. There are no significant differences in the age and gender of the patient at the time of the birth of the Modified Bass technique. Conclusions: The data conclude on the importance of knowledge and correction of the brushing technique as a determinant for the reduction of the biofilm.